Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2004
DOI: 10.1136/ard.2003.013052
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of adalimumab as monotherapy in patients with rheumatoid arthritis for whom previous disease modifying antirheumatic drug treatment has failed

Abstract: Objective: To evaluate the efficacy and safety of monotherapy with adalimumab in patients with RA for whom previous DMARD treatment has failed. Methods: In a 26 week, double blind, placebo controlled, phase III trial, 544 patients with RA were randomised to monotherapy with adalimumab 20 mg every other week, 20 mg weekly, 40 mg every other week, 40 mg weekly, or placebo. The primary efficacy end point was >20% improvement in the ACR core criteria (ACR20 response). Secondary efficacy end points included ACR50, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

18
293
6
17

Year Published

2005
2005
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 563 publications
(339 citation statements)
references
References 24 publications
(14 reference statements)
18
293
6
17
Order By: Relevance
“…The incidences of adverse events, serious adverse events, and infections were similar between treatment groups. Overall, the safety of adalimumab was similar to that reported in studies of adalimumab in RA (25)(26)(27) and to that reported in previous studies of other therapies in PsA (11,20,50,51).…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…The incidences of adverse events, serious adverse events, and infections were similar between treatment groups. Overall, the safety of adalimumab was similar to that reported in studies of adalimumab in RA (25)(26)(27) and to that reported in previous studies of other therapies in PsA (11,20,50,51).…”
Section: Discussionsupporting
confidence: 86%
“…Adalimumab (Humira; Abbott, Abbott Park, IL) is a fully human, anti-TNF monoclonal antibody that has been shown to have efficacy, when used alone or in combination with MTX, in patients with moderate-tosevere RA (24)(25)(26). Since adalimumab has the potential to be an effective treatment for PsA, the Adalimumab Effectiveness in Psoriatic Arthritis Trial (ADEPT) (Appendix A), a double-blind, randomized, placebocontrolled trial, was carried out to evaluate the safety and efficacy of adalimumab.…”
mentioning
confidence: 99%
“…The efficacy confirmed in the CHANGE study should be seen as such [18], since all the ADA-treated patients received ADA monotherapy. The results compared well to those of the DE011 monotherapy study conducted overseas [8]. The present HARMONY study is the first study to demonstrate the efficacy and safety of ADA therapy in combination with MTX in Japanese RA patients.…”
Section: Discussionsupporting
confidence: 74%
“…A recent meta-analysis on the effects of anti-TNF␣ therapy (12) excluded etanercept and included 2 studies (32,33) that compared adalimumab monotherapy with placebo (RR 6.3 and RR 15.3). Such an increase in the rate of serious infections is not unexpected when comparing an immunosuppressive agent with placebo; however, "no treatment" is an unrealistic strategy in clinical practice.…”
Section: Discussionmentioning
confidence: 99%